1980
DOI: 10.1002/1097-0142(19800715)46:2<408::aid-cncr2820460233>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of human breast lesions following experimental training

Abstract: This study was designed to evaluate the effect of breast examination training with silicone models on the detection of lesions in natural breast tissue. Six women with a total of 13 benign breast lumps were examined by 20 trainees before and after a 20--30 minute training session or a period of unrelated activity. Following the training, percentage of correct detections, duration of examination, and reports of false positives increased. Confidence in correct detections and false positives also increased, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
3

Year Published

1982
1982
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(42 citation statements)
references
References 10 publications
2
37
0
3
Order By: Relevance
“…Nurses and midwives were recruited and trained in the technique of CBE using the MAMMACARE TM10 programme tested previously in the Philippines, that uses silicone models of the breast for training purposes 11 and has been shown to enhance performance of examiners in previous studies. [12][13][14] Training was repeated for selected groups of examiners who missed or over-reported by 20% the lumps in the silicone models.…”
Section: Interventionmentioning
confidence: 99%
“…Nurses and midwives were recruited and trained in the technique of CBE using the MAMMACARE TM10 programme tested previously in the Philippines, that uses silicone models of the breast for training purposes 11 and has been shown to enhance performance of examiners in previous studies. [12][13][14] Training was repeated for selected groups of examiners who missed or over-reported by 20% the lumps in the silicone models.…”
Section: Interventionmentioning
confidence: 99%
“…Hall et al (1980) also compared the teaching for detection of tumours in silicone models and human breasts. Findings indicated that detection of breast lesions increased significantly in both formats.…”
Section: Breast Modelsmentioning
confidence: 99%
“…In the second report, the simple breast model was also used in a validation-field study (Hall, Stephenson, Adams, Goldstein, Pennypacker, & Stein, 1980). Before and after a brief experimental training session on the model with simulated lumps, 20 trainees examined six women with a total of 13 known benign breast lesions.…”
mentioning
confidence: 99%